Gender Justice: Implementation of Quotas for Female Representation Among Constitutional Court Judges in Indonesia - Baharuddin Riqiey; Avany Mahmudah; Sukardi Sukardi; Fersanda Batrysia Alaina (Mimbar Keadilan, 2026)
Since the Constitutional Court was established, male constitutional judges have always dominated the court. There have only been two female constitutional judges in Indonesia since the Constitutional Court was established. The absence of regulations regarding quotas for female representation among constitutional judges is one of the factors contributing to this situation. This certainly has the potential to cause gender inequality and prevent equal opportunities in government. Therefore, this study aims to examine and analyze the implementation of quotas for female representation among constitutional judges in Indonesia and its urgency. This research is legal research with a legislative, conceptual, case, and comparative approach. The results of this study show that practices in various countries, such as South Korea and Austria, have involved women in their constitutional courts. This is in contrast to Indonesia, which only involves one out of every nine constitutional judges. Therefore, it is necessary to regulate the representation of women in the Indonesian Constitutional Court to a minimum of 30% or one from each proposing institution. This is to: (i) create a constitutional practice in accordance with the mandate of Article 28D paragraph (3) and Article 28H paragraph (2) of the 1945 Constitution of the Republic of Indonesia; (ii) realize the objectives of the Sustainable Development Goals (SDGs); (iii) provide a women's perspective on the review of laws and regulations related to women and children; and (iv) achieve gender equality.